Psychobiological Effects of Prenatal Glucocorticoid Exposure in 10-Year-Old-Children - Erni, Katja; Shaqiri, Luljeta; La Marca, Roberto; Zimmermann, Roland; Ehlert, Ulrike (Frontiers in Psychiatry, 2012)
Background: Prenatal stress seems to have long-lasting effects on biological and psychological processes of the offspring. However, to date, there have been no studies investigating the effects of prenatal glucocorticoid exposure on psychological, endocrine, and autonomic responses to a standardized psychosocial stress test in children. Methods: A sample of 115 healthy, ten-year-old children was examined. The Glucocorticoids+Tocolytics group was characterized by tocolytic treatment of the mothers due to preterm labor (n=43). In addition, the pregnant women received glucocorticoid treatment in order to accelerate fetal lung maturation in case of preterm birth. The first control group (Tocolytics) consisted of children whose mothers also experienced preterm labor, but did not receive glucocorticoid treatment (n=35). In the second control group (CONTROL), children whose mothers had a complication-free pregnancy were assessed (n=37). Psychological parameters (stress appraisal and mood) using self-report questionnaires as well as salivary cortisol, salivary alpha-amylase and heart rate were measured during a standardized psychosocial stress test (TSST-C). Results: Group comparisons revealed that a subscale of stress appraisal, control expectancies, significantly differed in children who were prenatally exposed to glucocorticoids as compared to both control groups (F= 4.889, p = .009). Furthermore, significant differences between the groups were revealed for salivary cortisol. With respect to overall stress appraisal and heart rate, trends toward significance were observed between the three groups. Conclusions: At the age of ten, those children who have been exposed to prenatal maternal glucocorticoids show changed psychobiological stress reactivity to a standardized psychosocial stress test as compared to control children.